Etyka a kształtowanie rynkowego ładu gospodarczego w Polsce - Przybyciński, Tomasz (Annales. Etyka w Życiu Gospodarczym, 2010)
The social market economy respects economic and social values as well as ethics. However, the ethical dimension of the economic transformation has been neglected in Poland. That is just why positive consequences of the economic transformation have been reduced.